2013
DOI: 10.1021/ie3033312
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Polyacrylonitrile-2-aminothiazole Resin Synthesis, Characterization, and Its Adsorption Performance and Mechanism for Removal of Hg(II) from Aqueous Solutions

Abstract: A novel chelating resin, polyacrylonitrile-2-aminothiazole (PAN-AT), was synthesized simply by the reaction of polyacrylonitrile with 2-aminothiazole. Optimization of the PAN-AT synthesis was carried out at different temperatures, different molar ratios of reagents, and different time intervals in N,N-dimethylformamide (DMF) using response surface methodology (RSM) for the first attempt. The functional group capacity (the content of the functional group) and the percentage conversion of the functional group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 30 publications
3
46
0
Order By: Relevance
“…Also carbon content increased after acid activation showing the effectiveness of the acid treatment on the precursors. According to Xiong and coworkers only samples with high carbon content can be an efficient adsorbent for the removal of dye, heavy metals and other organic pollutant from aqueous solution (Xiong et al 2013). Effectiveness of the prepared adsorbent based on the carbon content in the removal of pollutant is in the order KNPA [ BHA [ CHA (Table 1).…”
Section: Energy Dispersive X-raymentioning
confidence: 99%
“…Also carbon content increased after acid activation showing the effectiveness of the acid treatment on the precursors. According to Xiong and coworkers only samples with high carbon content can be an efficient adsorbent for the removal of dye, heavy metals and other organic pollutant from aqueous solution (Xiong et al 2013). Effectiveness of the prepared adsorbent based on the carbon content in the removal of pollutant is in the order KNPA [ BHA [ CHA (Table 1).…”
Section: Energy Dispersive X-raymentioning
confidence: 99%
“…2 that the equilibrium state was not reached for 26 h. As the temperature increased from 288 to 318 K, the equilibrium adsorption capacity exhibited the same trend. A higher adsorption capacity at higher temperature suggests that the Ni(II) adsorption onto the 110-H resin is a temperature-dependent process [22].…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…Q 1 and Q 2 are the calculated adsorption capacities of the Lagergren firstorder model and the pseudo-second-order model (mg/g), respectively. The kinetic parameters are represented in Table 4, the experimental data for adsorption of Ni(II) on 110-H showed that the correlation coefficient (R 2 2 ) for the pseudo-second-order model is better than the correlation coefficient (R 1 2 ) for the Lagergren first-order model [22]. Moreover, the experimentally calculated capacity of the pseudo-second-order model generates good fittings which indicated that the interactions would follow the pseudo-second-order kinetics.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…Recently, it was reported that 2AT-functionalized polyacrylonitrile resin enabled separation and preconcentration of Hg(II) from multicomponent solutions containing Ni(II), Cu(II), Cd(II), Zn(II), and Pb(II) [12]. Also, 2AT-functionalized polystyrene exhibited an excellent selectivity for adsorption of Au(III) ions in the presence of Ni(II), Cu(II), Cd(II), and Co(II) interface ions in aqueous solutions [13].…”
Section: Introductionmentioning
confidence: 99%